The long term health effects of education - Vincent O'Sullivan (The Economic and Social Research Institute (ESRI), 2012)
Using data from The Irish Longitudinal Study on Ageing, I find that exogenous changes in the schooling of men born into lower social class families in Ireland during the late 1940s and 1950s had a statistically significant positive effect on their self-reported health in later life. I also find that the increased level of schooling had a statistically significant positive effect on physical exercise in later life as well as reducing the probability of an individual experiencing certain non-cardiovascular chronic conditions. However no statistically significant effect was found in relation to cardiovascular disease, self-rated mental health, smoking behaviour or self-reported and objectively measured memory although there is a high degree of imprecision in these estimates.
Keywords: 330